2017
DOI: 10.1002/fsn3.510
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestibility of hydrothermally modified Bambara groundnut (Vigna subterranean L.) starch and flour

Abstract: In‐vitro digestibility and functional properties of Bambara groundnut (Vigna subterranean) (BG) flour, and its native and hydrothermally modified starches were investigated. The isolated native starch (BNS) was modified by annealing at 50°C for 48 hr (BAS), and heat‐moisture treated at 100°C for 16 hr at 25% moisture level (BHS). The crude protein of BG flour was 16.88%. The amylose content of the flour and native starch was 6.10% and 27.70%, respectively. Hydrothermal modification increased the gelatinization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 58 publications
(109 reference statements)
3
15
0
Order By: Relevance
“…This is due to the action of heat‐moisture treatment which further restricts the swelling of the starch granules (Singh, Chang, Lin, Singh, & Singh, ). Afolabi, Opara, Kareem, and Oladoyinbo () reported reduction in the swelling power for hydrothermal modified bambara groundnut starches. The significance of this result means that high water penetration can be achieved for flours subjected to low incubation temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the action of heat‐moisture treatment which further restricts the swelling of the starch granules (Singh, Chang, Lin, Singh, & Singh, ). Afolabi, Opara, Kareem, and Oladoyinbo () reported reduction in the swelling power for hydrothermal modified bambara groundnut starches. The significance of this result means that high water penetration can be achieved for flours subjected to low incubation temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The trend of this result suggests that bambara groundnut had higher resistant starch content than breadfruit. Afolabi et al (2018) reported 33% resistant starch content for bambara groundnut flour. The difference in the resistant starch content of the two crops and their flour blends can be ascribed to differences in genetic composition, starch crystallinity, granular structure, amylose/amylopectin ratio, and interaction of starch with other macro and micro nutrients (Sajilata et al, 2006).…”
Section: Resistant Starch and In Vitro Starch Digestibilitymentioning
confidence: 99%
“…Starch is the most important edible polysaccharide containing nutritionally high to low molecular weight sugars [97]. Food industry uses starch as a thickening, bulking agent, gelling and for water holding capacity making it as a treasured factor [98]. Recent study documented that fully digested starch in small intestine is known as digestible starch, the incompletely digested starch in small intestine is known as partially digested starch, while starch that totally forbids digestion in small intestine is known as resistant starch [99].…”
Section: Tapioca/ Cassavamentioning
confidence: 99%